EFFICIENCY TESTING OF ELECTRIC ROTARY ACTUATORS WITH NON-STANDARD REDUCTION UNITS FOR LOWER LIMB EXOSKELETONS - Belogusev, Vladimir; Egorov, Aleksey (Journal of Applied Engineering Science, 2019)
The purpose of this paper is to develop a method and instruments for identifying the efficiency of an electric rotary actuator for an electromechanical orthosis of a lower limb exoskeleton, which greatly influences its weight and dimensions. The reduction units currently used as part of electric drives for exoskeletons are made in accordance with a non-standard form factor design, which impedes the use of existing methods and tools for measuring their torque and performance without considerable errors caused by mechanical losses in the bearing assemblies of test equipment. The method proposed in this paper solves this problem by identifying the values of decelerating torque associated with friction between bearing elements. In the experimental part of this work, the proposed method and the measuring system were evaluated, and it was found that the measurement error was about 1.2%, which slightly exceeds the total level of random and systematic errors of instruments applied when measuring the desired values. On the basis of the obtained results, it is possible to conclude that the developed method can be used to control the efficiency of electric rotary actuators for exoskeletons both at the stage of their production and during their operation.